THE INFLUENCE OF PRICE, ONLINE TRANSACTION SECURITY, AND PRODUCT QUALITY ON PURCHASING DECISIONS IN THE GROUP OF FACEBOOK FORUM JUAL BELI SURAKARTA CASUALS - Kim Budiwinarto; Juni Trisnowati; Ambyah Atas Aji; Aldi Pratama (Widya Dharma Journal of Business - WIJoB, 2026)
This research is a quantitative research. This study aims to determine the effect of price, online transaction security, and product quality on purchasing decisions in the Surakarta Casual Buy and Sell Forum Facebook group. This study uses primary data whose data collection is done by distributing questionnaires via Google Form. This study uses validity and reliability tests, classic assumptions tests, multiple linear regression analysis, and coefficient of determination analysis with the help of SPSS. The sample used in this study was 100. The results of the study obtained using the t-test and F-test show that price has a positive effect on purchasing decisions, online transaction security has a positive effect on purchasing decisions, and product quality has a positive effect on purchasing decisions and price, online transaction security, and product quality have a positive effect simultaneously on purchasing decisions. In the coefficient of determination test, the data results were 53.2%, which can be explained by price, online transaction security, and production quality, while the remaining 46.8% can be explained by the influence of other variables not studied by the author.